SAFETY AND SECURITY OF WOMEN ON TRANSPORT: A CASE OF RIDE-HAILING SERVICES IN GAUTENG, SOUTH AFRICA - Babra DURI (Scientific Journal of Silesian University of Technology. Series Transport)
Women, particularly in developing countries, rely heavily on public transport for their daily commute. This study explores the safety and security of women using ride-hailing services in Gauteng. Specifically, the study seeks to understand women’s experiences using ride-hailing services, which might influence their mobility. This study employed a constructivist research philosophy, utilizing qualitative, semi-structured interviews to explore the experiences of women who use ride-hailing services. The study findings reveal several disturbing incidents reported by female passengers using ride-hailing services; however, it is important to note that not all drivers exhibit inappropriate behaviour. Some drivers make inappropriate remarks, while others exhibit rude behaviour. The study found that some drivers use longer routes, leading to higher fares, which can be seen as exploitation. The study also reports some incidents where ride-hailing drivers almost kidnapped some female passengers, indicating a severe safety concern. The study contributes to the ongoing discourse on gender and transport studies, providing empirical evidence on the experiences of women using ride-hailing services in Gauteng, South Africa.